Influence of El Niño and La Niña on the population dynamics of Calanus chilensis in the Humboldt Current ecosystem of northern Chile - Escribano, R.; Hidalgo, P. (ICES journal of marine science, 2000)
From a time-series of sea surface temperature (SST) and zooplankton data from December 1991 through January 1998, and using a temperature-dependent model, we studied the growth rate (g), female size, generation time (GT), and number of generations per year of Calanus chilensis from the Mejillones Peninsula, northern Chile. Female size was negatively related to SST on both seasonal and interannual scales, and abundance was positively correlated to SST through seasons, though not associated with warm (El Niño) or cold (La Niña) years. The model predicted that cold and warm years may have a substantial effect on annual abundance of this species. Mean annual abundances of C. chilensis were not consistent with those predicted by the model, however, suggesting that factors other than temperature may regulate interannual differences in population size. For instance, changes in mortality rates between warm and cold years and advective losses under strong coastal upwelling may be implicated in the variation. Despite smaller population size in years subject to ElNiño conditions, predicted annual means of g and GT showed little variability, as expected for fairly stable/constant annual mean SST. The overall g was 0.33 d−1, while GT was 18.1 d under an overall mean SST of 17.7°C. The lack of evidence for food-shortage effects during El Niño conditions and the influence of temperature on a seasonal scale suggest that temperature-dependent growth may be a mechanism regulating population size by adjusting growth and development to stable temperature regimes on an annual basis.